Pengaruh Persepsi Kegunaan, Kemudahan Penggunaan dan Norma Subyektif pada Minat Berperilaku Penggunaan E-Billing - Ratnadi, Ni Made Dwi; Widanaputra, Anak Agung Gde Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p03, 2019)
This study aims to examine the behavior of individual taxpayers that use e-billing. The study was conducted at the Primary Tax Office in the Province of Bali. Data was collected using surveys. The sample was selected using convenience non-probability sampling technique. The number of respondents analyzed was 120 people. A variance based structural equation modeling approach with the calculation process supported by the partial least square was used in data analysis. The results show that perceived usefulness has a positive effect on attitude toward using e-billing, ease of use has a positive effect on attitude toward e-billing, ease of use has a positive effect on the perceived usefulness. The attitude and subjective norms positively influence the interest of individual taxpayers in using the e-billing system in paying taxes. Keyword: E-billing, perceived ease of used, usefulness, attitude